PENGARUH GREEN ACCOUNTING, GREEN INNOVATION, DAN ENVIRONMENTAL PERFORMANCE TERHADAP NILAI PERUSAHAAN - Callista Reva; Julianti Sjarief (Jurnal Akuntansi, 2026)
This study aims to analyze the influence of green accounting, green innovation, and environmental performance on firm value. The population of this research is companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. The data used are secondary data that were taken from financial, annual, and sustainability reports. The sample selection in this study used a purposive sampling method and resulted in 95 data samples. The data analysis methods used were descriptive statistics and multiple linear regression. Data processing was conducted using the IBM Statistical Package for the Social Sciences Statistics (SPSS) 26. With a significance level of 5%, the results of the study indicate that green accounting has no effect on firm value, whereas green innovation and environmental performance have a positive effect on firm value.